(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: The purpose of this paper is to investigate the effect of the lean concept on organizational learning in the real estate industry. The objectives are to determine the impact of the lean concept on knowledge and leadership and evaluate the challenges affecting the implementation of lean and provide recommendations to remedy the situation. Design/Methodology/Approach: The study employed a quantitative method. Questionnaires were used to measure the variables. A five-point Likert scale was used for both lean thinking to measure the various perspectives and dimensions. The questionnaires were administered to 200 respondents drawn from the real estate industry in Ghana using a simple random sampling technique. The data collected was then summarized through relevant thematic areas and analyzed statistically through descriptive statistics, correlations and multiple regression to establish the nexus between lean concept and organizational learning with help of SPSS version 22. Findings: The finding of the study established that lean thinking affects organizational learning except for experience sharing. The findings also revealed that the lean concept has a positive effect on development, leadership and organizational culture. Research Limitations: The study focused on the effects of lean thinking on organizational learning in the real estate industry in Ghana. Hence the questionnaires were administered mainly to 200 companies in the real estate industry in Ghana. Practical Implication: The knowledge advanced in this study will help managers of real estate companies as a matter of necessity embrace lean thinking if they are to meet customer-focused requirements, remain profitable and shorten the duration of construction projects, waste elimination and cost reduction. Originality/Value: This paper is focused on the effects of lean principles on organizational learning in the real estate industry with a positive impact on organizational development, leadership and organizational culture.